2014
DOI: 10.1186/1756-0500-7-328
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcal meningitis presenting with bilateral complete ophthalmoplegia: a case report

Abstract: BackgroundCryptococcus neoformans is saprophytic encapsulated yeast. Infection is acquired by inhalation of the organism and could be asymptomatic or limited to the lungs, specially in the immunocompetent host. Cryptococcal meningitis is a serious opportunistic infection among post transplant recipients. Cranial nerve palsies and ophthalmoplegia are well known complications of this disease, but bilateral complete ophthalmoplegia is a very rare presentation.Case PresentationA Sri Lankan young male, who is a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Loss of vision, diplopia and ocular motility deficit have been reported previously (5)(6)(7). In the present study, a female immunocompetent patient with CM is reported who initially presented with eye symptoms, and subsequently fully recovered with complete resolution of the initial symptoms following combined treatment with amphotericin B and fluconazole.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…Loss of vision, diplopia and ocular motility deficit have been reported previously (5)(6)(7). In the present study, a female immunocompetent patient with CM is reported who initially presented with eye symptoms, and subsequently fully recovered with complete resolution of the initial symptoms following combined treatment with amphotericin B and fluconazole.…”
Section: Introductionsupporting
confidence: 66%
“…Such impaired patients include those with a malignancy, connective tissue disorder, HIV infection or those who have undergone organ transplantation (2,14). However, previous studies have shown that a number of patients infected with Cryptococcosis are immunocompetent (6,(15)(16)(17). CM causes morbidity and mortality worldwide, particularly in patients with impaired cell-mediated immunity; however, the clinical outcomes in immunocompetent patients are more favorable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary involvement is also common 2. Lesions have also been described in the brain, lungs, skin, bloodstream,2 3 kidneys,4 prostate,5 6 eyes,7 sinuses,8 colon,9 liver10 and blood vessels as vasculitis 16…”
Section: Discussionmentioning
confidence: 99%
“…It is the third leading cause of fungal infection in solid organ transplant recipients, following aspergillosis and candidiasis, with an overall incidence of 2.8% in this population 2 3. Cases most frequently involve the central nervous system or the lungs, but multiple other sites of infection have been documented including the skin, bloodstream,2 3 kidneys,4 prostate,5 6 eyes,7 sinuses,8 colon9 and liver 10. About 5% of all cryptococcal infections present with osteomyelitis 11.…”
Section: Introductionmentioning
confidence: 99%